Establishing key factors for successful mussel biobanking - Campos Rosende, Sara; Costas, Damián; Troncoso, Jesús; Paredes, Estefanía (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):299